New Cartographies, Nomadic Methodologies - Goarzin, Anne,Parsons, Maria (Peter Lang Ltd, International Academic Publishers, 2020)
Introduction: New Materialist Encounters Anne Goarzin and Maria ParsonsPart I Artistic Intra-actionsForce of Nature: Earth Stories (a Conversation with Lisa FitzGerald) Siobhán McDonaldDiffractive Practice: Supercollisions in Art and Science (a Conversation with Maria Parsons) Sinéad McDonaldCONTAGION Rachel Gallagher, Jack Hogan and Moira TierneyThe Plurality of Existence in the Infinite Expanse of Space and Time Clodagh EmoePart II Bodies, Performance, Memory‘Dirty matter’: New Material Terrains in Irish Poetry Anne KarhioMaterial Bodies: Three Performance-Based Interventions in the Irish Landscape Lisa FitzGerald ‘Choreographies of becoming’ in Mia Gallagher’s Beautiful Pictures of the Lost Homeland (2016) Fiona McCann Part III Shared Places and Diffracted Voices Fractured Liminality in Kabosh’s Green and Blue and Lives in Translation Eva Urban-Devereux Narrative 4 Story Exchanges: Fostering Empathy Marie Mianowski Performing Jazz and Sharing Creative Spaces: An Interview with David Lyttle Fabrice Mourlon This volume embraces the critical turn of new materialism in order to address how creative and social practices allow for the definition of alternative subject positions and to examine how power relations operate at an embodied, relatable level: it proposes to think global but act local. The contributions by scholars and artists offer new ways of engaging and understanding Ireland’s contemporary political, activist and artistic landscape. They open up onto epistemological ways of considering not only the inventions of creative and scholarly research and practice, but also invention and experimentation itself. The volume provides a space for conversation and brings out the potential of non-linear thinking by bringing together artists and scholars to consider the materiality of identity and place through the body, migrancy, ecology and digital technologies. The contributors draw new maps, making new connections, diffracting Irish social imaginaries. This multidisciplinary collection proposes strategies and methods to ethically respond to and engage with the complex situations and urgent challenges that preoccupy our contemporary present. There is something in this book for both the specialist and non-specialist alike and it is essential reading for anyone with an interest in new methodologies in Irish studies
9781789973655
Keywords: Aufsatzsammlung